Pengembangan instrumen literasi matematis kontekstual berbasis kearifan lokal untuk siswa SMP - Kusumastuti, Fitri Anisa; Lutfi, Muh. Khaedir; Saleh, Sitti Fithriani; Lailia, Trisna Chairul (Karoteh Utama, 2025)
This study aims to develop a contextual mathematical literacy instrument based on local wisdom that is valid, reliable, and practical for junior high school students. The development of this instrument was motivated by the limited availability of assessment tools capable of measuring students’ mathematical literacy comprehensively and in alignment with their cultural contexts. The research employed the ADDIE development model, consisting of five stages: analysis, design, development, implementation, and evaluation. The study involved 30 students from a junior high school in Tangerang Regency. Data were collected through written tests, expert validation sheets, classroom observations, and practicality questionnaires. The results of expert validation showed an average score of 4.65, indicating that the instrument is highly valid. Field trials revealed a reliability coefficient of α = 0.89, suggesting high internal consistency. Furthermore, the practicality and acceptability levels reached 88.7% and 90.3%, respectively, both categorized as very good. These findings indicate that the developed contextual mathematical literacy instrument based on local wisdom is feasible for use as an authentic assessment tool to evaluate students’ mathematical literacy skills in a meaningful and culturally relevant manner.